Genetic diversity of Ehrlichia canis in dogs from Turkey inferred by TRP36 sequence analysis and phylogeny - Aktas, Munir; Ozubek, Sezayi (Elsevier Sci Ltd, 2019)
Canine monocytic ehrlichiosis, an important tick-borne disease caused by Ehrlichia canis, is cosmopolitan but particularly prevalent in tropical and subtropical regions. In Turkey, the genetic diversity of E. canis remains undefined. The aim of this study was to characterize E. canis in naturally infected dogs from Turkey by sequencing and phylogenetic analysis of the Tandem Repeat Protein 36 (TRP36) encoded by the trp36 gene. A total of 167 archived blood samples randomly collected from municipal shelter dogs in three distinct geographic regions were analyzed for E. canis. Only ten samples (5.98%) were found positive by PCR assays target regions of the trp36 and 16S rRNA genes. Sequence analysis of Turkish E. canis TRP36 revealed five Tanden Repeat sequences (TRs) resulting to three TR genotypes: i) the previously reported US genotype composed exclusively from TRs of TEDSVSAPA sequence (14 or 8 TRs), ii) the previously Brazilian genotype composed exclusively from TRs of ASVVPEAE sequence (13 TRs), and iii) a novel genotype. In addition, phylogenetic analysis based on the entire sequences of TRP36 revealed that these genotypes correspond to four distinct genogroups (US genogroups I and II, Brazilian genogroup and Costa Rica-Turkey genogroup), all containing Turkish genotypes amongst other geographically distant E. canisgenotypes.
Keywords: Ehrlichia canis; trp36 (gp36) gene; Tandem repeat; Genogroup; Dog